What is counted counts: An innovative linkage of police, hospital, and spatial data for transportation injury prevention. (December 2022) - Soltani, Shamsi; Schwarcz, Leilani; Morris, Devan; Plevin, Rebecca; Dicker, Rochelle; Juillard, Catherine; Nwabuo, Adaobi; Wier, Megan
Highlights: Standard surveillance differentially undercounts transportation injuries & severity. Linked medical and police data capture critical injuries otherwise missed. Hospital sources improve estimates among vulnerable road users and people of color. Linkage lends evidence for engineering, infrastructure prioritization & education. Abstract: Introduction: Growing research indicates transportation injury surveillance using police collision reporting alone underrepresents injury to vulnerable groups, including pedestrians, cyclists, and people of color. This reflects differing reporting patterns and non-clinicians' challenge in accurately evaluating injury severity. To our knowledge, San Francisco is the first U.S. city to link and map hospital and police injury data. Analysis of linked data injury patterns informs interventions supporting traffic fatality and injury prevention goals. Methods: Injury and fatality records 2013–2015 were collected from San Francisco Police, Emergency Medical Services (EMS), Medical Examiner, and Zuckerberg San Francisco General Hospital (ZSFG). Probabilistic linkage was conducted using LinkSolv9.0 on match variables collision/admission time, name, birthdate, sex, travel mode, and geographic collision location. Results: From 2013-2015, this study identified 17, 000+ transportation-related injuries on public roadways in San Francisco. Twenty-six percent (n = 4, 415) appeared in both police and ZSFG sources. Linked injury records represent 39% of police records (N = 11, 403) and 43% of hospital records (N = 10, 223). Among hospital records, 34% of cyclist, 38% of motor vehicle occupant, 61% of pedestrian, and 54% of motorcyclist records linked with a police record. Linkage rate varied by travel mode even after controlling for injury severity. Transportation-injured ZSFG-treated patients lacking police reports were more often cyclists, male, Hispanic or Black, and less often occupants of motor vehicles compared to those with injuries captured only in police reports. Conclusions: Incorporating hospital and EMS spatial data into injury surveillance systems historically reliant on police reports offers trifold benefits. First, linkage captures injuries absent in police data, adding data on populations empirically vulnerable to injury. Second, it improves injury severity assessment. Finally, linked data better informs and targets interventions serving injury-burdened populations and road users, advancing transportation injury prevention. Practical applications: Linkage closes data gaps, improving ability to quantify injury and develop evidence-based interventions for vulnerable groups.